2021
DOI: 10.1158/2159-8290.cd-20-0331
|View full text |Cite
|
Sign up to set email alerts
|

The RNA m6A Reader YTHDF2 Maintains Oncogene Expression and Is a Targetable Dependency in Glioblastoma Stem Cells

Abstract: Glioblastoma (World Health Organization grade IV glioma) represents the most common primary, intrinsic brain tumor with inevitable recurrence, limiting the median survival of patients to little more than a year ( 1, 2 ). Glioblastomas display cellular hierarchies with self-renewing glioblastoma stem cells (GSC) at the apex, with contributions of GSCs to therapeutic resistance and tumor recurrence ( 3-5 ). Standard-of-care therapy includes surgical resection followed by combined radiotherapy and chemotherapy, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
197
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 264 publications
(224 citation statements)
references
References 80 publications
13
197
1
1
Order By: Relevance
“…Readers can decode m 6 A methylation information and convert it into effectors of functional signals. Recently, increasing evidence has shown that changes in m 6 A regulators can promote the development of several cancers ( 20 ), including glioblastoma, breast and cervical cancers, liver and gallbladder cancers, and bladder and prostate cancers ( 21 23 ). However, despite some progress in revealing their role in multiple cancers, the characteristics of m 6 A modification in HNSCC are still very inadequate.…”
Section: Introductionmentioning
confidence: 99%
“…Readers can decode m 6 A methylation information and convert it into effectors of functional signals. Recently, increasing evidence has shown that changes in m 6 A regulators can promote the development of several cancers ( 20 ), including glioblastoma, breast and cervical cancers, liver and gallbladder cancers, and bladder and prostate cancers ( 21 23 ). However, despite some progress in revealing their role in multiple cancers, the characteristics of m 6 A modification in HNSCC are still very inadequate.…”
Section: Introductionmentioning
confidence: 99%
“…According to MODOMIC, a comprehensive database resource for systems biology of RNA modi cation, 172 different RNA chemical modi cations have been found to date in all living organisms, including m6A, which is the most abundant and reversible modi cation, as well as m5C and m7G, Am, Gm and others [13]. Recent studies have demonstrated that various types of cancers, including cervical cancer, hepatocellular carcinoma and glioblastoma, are associated with abnormal m6A abundance [14][15][16]. We characterized the speci c m6A methylation changes and related signaling pathways in Wilms' tumor through experimental and bioinformatics analyses.…”
Section: Discussionmentioning
confidence: 99%
“…ZC3H13 was downregulated in colorectal cancer and found to suppress proliferation and invasion via inactivating Ras-ERK pathway [38]. The overexpression of YTHDF2 was observed in liver cancer, AML and GBM, which was implicated in the stemness maintenance of cancer stem cells [19,39,40]. HNRNPA2B1 was highly expressed in multiple types of cancer, and it promoted the proliferation of breast cancer cells through STAT3 pathway [41].…”
Section: Discussionmentioning
confidence: 99%